Проблеми етнічної , мовної та конфесійної ідентичності українців у повітах Марамуреш та Сату Маре (Румунія) - Зан, М. (Народна творчість та етнографія, 2009)
The problem of ethnical, linguistical and religious identity of Ukrainians of Maramuresh and Satu Mare districts (Romania). In the article has analyzed of the problems of ethnical, linguistical and religious identity of the Ukrainians of Maramuresh and Satu Mare districts of Romania. A conclusion is made concerning to the discrepancy of identification of Ukrainian group. The author emphasize about the artificiality of Ruthenians identity in this region. It was concluded that refusal of native language and orthodox religion give rize to assimilation of Ukrainian national minority of Romania.